COMPARATIVE ANALYSIS OF STUDENTS’ SCORES IN SOCIAL STUDIES AND INTEGRATED SCIENCE AT JUNIOR SECONDARY SCHOOL CERTIFICATE EXAMINATION IN EDU LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA - Adebayo, Awoniyi Samuel; Dorcas, Awoniyi Tinuola (European Scientific Journal, ESJ, 2015)
The study compared the scores of students in Social Studies and Integrated Science at the Junior Secondary School Certificate Examination (JSSCE) in Edu Local Government Area (LGA) of Kwara State, Nigeria. The research design was correlational for which the t-test and one –way analysis of variance (ANOVA) were employed. The sample for the study consisted of all students who sat for the 2011, 2012 and 2013 JSSCE in six out of the eleven Junior Secondary Schools in the Local Government Area. The five schools were selected using the simple random sampling technique and all the 1,689 students who sat for the JSSCE in both subjects in the three years aforementioned were used for the study.The scores of students in both Social Studies and Integrated Science were obtained directly from the Junior Secondary School Certificate Examination result sheets from Principals of the selected schools. These were used as measures of academic performance. The data collected were analysed using the descriptive statistics, t-test and one way Analysis of Variance (ANOVA). The result revealed that there existed significant differences in the performances of male and female students in both Social Studies and Integrated Science in year 2011 with female students out performing their male counterparts however, there are no significant differences in male and female students’ performance in the two subjects in years 2012 and 2013.The multiple comparisons revealed that the scores of students in Social Studies were significantly different between years 2011 and 2012, 2011 and 2013 as well as between 2012 and 2013. In the same vein, the scores of students in Integrated Science for 2011and 2012 as well as 2011 and 2013 were found to be significant.